Increased diagnosis of enlarged vestibular aqueduct by multiplex PCR enrichment and next‐generation sequencing of the SLC26A4 gene. Issue 8 (25th June 2021) - Tian, Yongan; Xu, Hongen; Liu, Danhua; Zhang, Juanli; Yang, Zengguang; Zhang, Sen; Liu, Huanfei; Li, Ruijun; Tian, Yingtao; Zeng, Beiping; Li, Tong; Lin, Qianyu; et al.
Abstract: Background: The enlarged vestibular aqueduct (EVA) is the commonest malformation of inner ear accompanied by sensorineural hearing loss in children. Three genes SLC26A4, FOXI1, and KCNJ10 have been associated with EVA, among them SLC26A4 being the most common. Yet, hotspot mutation screening can only diagnose a small number of patients. Methods: Thus, in this study, we designed a new molecular diagnosis panel for EVA based on multiplex PCR enrichment and next‐generation sequencing of the exon and flanking regions of SLC26A4 . A total of 112 hearing loss families with EVA were enrolled and the pathogenicity of the rare variants detected was interpreted according to the American College of Medical Genetics and Genomics (ACMG) guidelines. Results: Our results showed that 107/112 (95.54%) families carried SLC26A4 biallelic mutations, 4/112 (3.57%) carried monoallelic variants, and 1/112 (0.89%) had none variant, resulting in a diagnostic rate of 95.54%. A total of 49 different variants were detected in those patients and we classified 30 rare variants as pathogenic/likely pathogenic, of which 13 were not included in the Clinvar database. Conclusion: Our diagnostic panel has an increased diagnostic yield with less cost, and the curated list of pathogenic variants in the SLC26A4 gene can be directly used to aid the genetic counseling to patients. Abstract : We designed a new molecular diagnosis panel for EVA based on multiplex PCR enrichment and next‐generation sequencing of the exon and flanking regions of SLC26A4. This strategy can not only greatly save time and reagents, but also provide more accurate diagnostic information for EVA patients.